Angiogênese, vascularização e uso do ultrassom Doppler colorido como ferramenta de avaliação das estruturas ovarianas - Ayres, Henderson; Mingoti, Gisele Zoccal [UNESP] (My University, 2012)
Angiogenesis occurs as a physiologic process and is essential for normal growth and development of tissue. The ovary and its structures need adequate vascular network to ensure the availability of oxygen, nutrients, hormones, substrate, and ensure the transfer of different hormones to target cells. Then, the proper formation of this network is a limiting step for the proper functioning of this organ in general. In recent years, the local blood flow of the ovary, has been examined by color Doppler ultrasound, being able to analyze the individual follicles and the corpus luteum. This review will board the relevant aspects of the restructuring vascular ovary during the estrous cycle in female domestic large.

A angiogênese ocorre como um processo fisiológico essencial para o crescimento e o desenvolvimento normal dos tecidos. A adequada formação da rede vascular é um passo limitante para o bom funcionamento do ovário, pois garante a disponibilidade de oxigênio, nutrientes, hormônios e substratos, bem como a transferência de diferentes hormônios para as células-alvo. Nos últimos anos, o fluxo sanguíneo local do ovário tem sido analisado por meio da ultrassonografia com Doppler colorido, técnica que permite analisar individualmente os folículos e o corpo lúteo. Esta revisão de literatura aborda os mais relevantes aspectos da reestruturação vascular do ovário durante o ciclo estral em fêmeas domésticas de grande porte.
Angiogenesis, vascularization and color Doppler ultrasonography to evaluate ovarian structures
Keywords: Angiogenesis; Vascularization; Doppler ultrasound; Ovarian structures; Angiogênese; Vascularização; Ultrassom Doppler; Ovário